The educational views of Dr. Vitaliano Bernardino - Portugal, Virginia P. (s.n.], 1971)
This paper analyzed the educational views of Dr. Vitaliano Bernardino. To make a clear and understandable presentation of the subject, the researcher limited the problem to the following major areas: his views on the educational mandate of the Constitution, on some aspects of the Philippine educational system, on some educational issues, and his views on the teacher and relevances of his educational views to some aspects of contemporary Philippine education.